Puerarin inhibits titanium particle‐induced osteolysis and RANKL‐induced osteoclastogenesis via suppression of the NF‐κB signaling pathway. Issue 20 (7th September 2020) - Tang, Wenkai; Xiao, Long; Ge, Gaoran; Zhong, Mengdan; Zhu, Jie; Qin, Jialin; Feng, Chencheng; Zhang, Wenhao; Bai, Jiaxiang; Zhu, Xuesong; Wei, Minggang; Geng, Dechun; et al.
Abstract: Osteolysis around the prosthesis and subsequent aseptic loosening are the main causes of prosthesis failure. Inflammation due to wear particles and osteoclast activation are the key factors in osteolysis and are also potential targets for the treatment of osteolysis. However, it is not clear whether puerarin can inhibit chronic inflammation and alleviate osteolysis. In this study, we investigated the effect of puerarin on Ti particle‐induced inflammatory osteolysis in vivo in rat femoral models and in vitro in receptor activator of nuclear factor kappa‐B ligand (RANKL)‐induced osteoclast activation models. Our in vivo results showed that puerarin significantly inhibited Ti particle‐induced osteolysis and the expression of matrix metallopeptidase 9 (MMP‐9), nuclear factor of activated T cells 1 (NFATc1), tumour necrosis factor (TNF)‐α and interleukin (IL)‐6. In vitro, puerarin prevented RANKL‐induced osteoclast differentiation, bone resorption and F‐actin ring formation in a concentration‐dependent manner. Furthermore, puerarin decreased the phosphorylation of p65 and prevented p65 moving from the cytoplasm to the nucleus. Puerarin also reduced the expression of osteoclast‐specific factors and inhibited the inflammatory response. In conclusion, our study proves that puerarin can block the NF‐κB signalling pathway to inhibit osteoclast activation and inflammatory processes, which provides a new direction for the treatment of osteolysis‐related diseases.